2011
DOI: 10.1021/pr200863r
|View full text |Cite
|
Sign up to set email alerts
|

Plant Cell Organelle Proteomics in Response to Abiotic Stress

Abstract: Proteomics is one of the finest molecular techniques extensively being used for the study of protein profiling of a given plant species experiencing stressed conditions. Plants respond to a stress by alteration in the pattern of protein expression, either by up-regulating of the existing protein pool or by the synthesizing novel proteins primarily associated with plants antioxidative defense mechanism. Improved protein extraction protocols and advance techniques for identification of novel proteins have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(102 citation statements)
references
References 91 publications
2
96
0
4
Order By: Relevance
“…In response to abiotic stress factors, plants may also accumulate and/or synthesize protein types (such as heat shock proteins (HSPs), zinc-finger proteins, mitogen-activated protein kinase (MAPK), late embryogenesis abundant (LEA) proteins; dehydrins, late embryogenesis abundant (LEA) proteins, chaperones, etc.). These proteins have been evidenced to help plants to run cellular metabolism and eventually to tolerate potential abiotic stress impacts (reviewed by Timperio et al 2008;Fatehi et al 2012;Hossain et al 2012;Ghosh and Xu 2014). However, owing to their great abundance and high rate constants of a range of reactive radicals, proteins are one of the major cellular constituents targeted by ROS (Davies 2005).…”
Section: Overviewmentioning
confidence: 99%
“…In response to abiotic stress factors, plants may also accumulate and/or synthesize protein types (such as heat shock proteins (HSPs), zinc-finger proteins, mitogen-activated protein kinase (MAPK), late embryogenesis abundant (LEA) proteins; dehydrins, late embryogenesis abundant (LEA) proteins, chaperones, etc.). These proteins have been evidenced to help plants to run cellular metabolism and eventually to tolerate potential abiotic stress impacts (reviewed by Timperio et al 2008;Fatehi et al 2012;Hossain et al 2012;Ghosh and Xu 2014). However, owing to their great abundance and high rate constants of a range of reactive radicals, proteins are one of the major cellular constituents targeted by ROS (Davies 2005).…”
Section: Overviewmentioning
confidence: 99%
“…2) (Bolwell et al, 2004;Cánovas et al, 2004;Figeys, 2003;Hennig, 2007) including studies of the relationships between proteins and plant development, seed maturation, responses to biotic and abiotic stresses and human allergies (e.g. Chen and Harmon, 2006;Hossain et al, 2012;Komatsu et al, 2012;Kosová et al, 2011;Sergeant and Renaut, 2010;Taká c et al, 2011;Timperio et al, 2008;Zhang et al, 2012). Many plants have been studied including A. thaliana, tobacco, vegetables, fruits and cereals.…”
Section: Plants Proteins In Generalmentioning
confidence: 99%
“…We recently reviewed plant cell organelle proteomics in response to abiotic stress 180 . A number of subcellular proteomics studies (gel-free or gel based) on soybean have been already reported.…”
Section: Subcellular Proteomics Of Soybeanmentioning
confidence: 99%